Corrosion crack failure analysis of 316L hydraulic control pipeline in high temperature aerobic steam environment of heavy oil thermal recovery well. (August 2022) - Li, Hai; Liu, Wei; Chen, Longjun; Fan, Pengcheng; Dong, Baojun; Ma, Zenghua; Wang, Tong
Highlights: Fixture for stress loading of hydraulic control pipeline is designed. Temperature affects the compactness of corrosion products on the surface of liquid control pipeline and the content of hydroxide in oxide film. The temperature of injection steam range is proposed to avoid the stress cracking of hydraulic control pipeline. Abstract: The 316L hydraulic control pipeline (HCP) easily caused corrosion failure in the process of heavy oil recovery. In this study, the corrosion failure of 316L HCP in the 260–350 °C high temperature aerobic steam environment was investigated by using autoclave. Based on SEM, EDS, cracks morphology and XPS analysis, the failure mechanism of 316L HCP exposure in different high temperature steam environments was concluded. The results indicate that the corrosion fracture occurs at 260 °C. The SCC cracking was transgranular propagation, and the corrosion failure was attributed to anodic dissolution stress corrosion cracking. With the increase of temperature, the formation of absorbed water film on the surface contributes to improving the compactness of corrosion products which could prevent the crack propagating under corrosion medium. Moreover, the high temperature significantly affected the content of Cr(OH)3 and Ni(OH)2 in the oxide film which improved the corrosion resistance of stainless steel.